Q. 565.0( 2 Votes )
Answer each of th
Given cos (tan-1 x + cot-1 √3) = 0
⇒ cos (tan-1 x + cot-1 √3) = cos (π/2)
⇒ tan-1 x + cot-1 √3 = π/2
We know that tan-1 x + cot-1 x = π/2
∴ x = √3
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation